Unraveling meteorologically influenced recurrence and sequential infection risks among influenza, mumps, scarlet fever, and hand-foot-and-mouth disease: evidence from Shenzhen, China - Hongxin Lyu; Huawei Xiong; Jue Liao; Lifang Cai; Yanpeng Cheng (Frontiers in Public Health, 2026)
Background Meteorological factors are key triggers for infectious diseases in high-density cities, yet their influence on the acute disease patterns of influenza, mumps, scarlet fever, and hand-foot-and-mouth disease (HFMD) remains unclear. This study aims to reveal the variations in relative risk and secondary infection associated with meteorological factors, thereby providing clues for further confirmatory research. Methods We analyzed city-wide incidence data from 2012 to 2020 alongside daily meteorological observations. Distributed lag non-linear models (DLNM) were used to quantify exposure-lag-response relationships. Andersen-Gill models assessed effects on disease recurrence, and Cox models evaluated risks of sequential infections between disease pairs, stratified by season. Results The peak-risk temperatures were 14.5 °C for influenza, 18.5 °C for mumps, 17 °C for scarlet fever, and 28.5 °C for hand-foot-and-mouth disease (HFMD). Average temperature (AT) increase raised influenza recurrence risk (e.g., 1.3% higher risk per 1 °C in children aged 0–14 years). Greater temperature variability reduced sequential infection risk for influenza after HFMD in the cold season (Hazard Ratio [HR] = 0.16) and warm season (HR = 0.14). Increased diurnal temperature range also lowered this risk in the cold season (HR = 0.09). Higher AT in warm season reduced sequential infection risks from influenza to HFMD (HR = 0.61). Increased relative humidity was protective in the cold season but became a risk factor in the warm season in specific disease. Conclusion Meteorological factors are pivotal in modulating the dynamics of common infections, and influencing both recurrence and sequential transmission. The protective effect of increased temperature variability against secondary infections highlights a complex climate-susceptibility interaction at the population level.